The Relationship between Passengers’ Satisfaction of Urban Road Transport Services and Their Sense of Belonging - Alborzi, Pezhman (Environmental Management and Sustainable Development, 2021)
Passengers’ satisfaction of urban road transportation services has been widely researched over the past few decades. However, no study has been conducted to analyze the relationship of the passengers’ satisfaction of regular taxi and bus transport services with an external psychological factor. To this end, 100 passengers were randomly recruited to participate in this study. The participants were required to complete three questionnaires to assess their level of belonging and their satisfaction of regular taxi and bus transport services as two prominent urban road transport services. The questionnaire of sense of belonging had 12 items rated on a 5-point Likert Scale. The responses also were rated from “strongly disagree” to “strongly agree”. The respondents were requested to grade 1 to 10 an 18-travel-attribute survey to assess their satisfaction of urban road transport services. The results indicated that passengers were not satisfied with urban road transport services; however, their satisfaction with regular taxi was higher in comparison with bus transport services. The findings also revealed that there was a significant correlation between the passengers’ level of belonging and their satisfaction of public transport services.